Collecting Patient Feedback as a Means of Monitoring Patient Experience and Hospital Service Quality – Learning from a Government-led Initiative - Han S; Xu M; Lao J; Liang Z (Patient Preference and Adherence, 2023)
Sirou Han,1,2 Min Xu,1 Jiahui Lao,3 Zhanming Liang4 1Hospital Administration Department, The Second Affiliated Hospital of Shandong First Medical University, Taian, People’s Republic of China; 2School of Public Health, Shandong First Medical University (Shandong Academy of Medical Sciences), Jinan, People’s Republic of China; 3Center for Big Data Research in Health and Medicine, The First Affiliated Hospital of Shandong First Medical University & Shandong Provincial Qianfoshan Hospital, Jinan, People’s Republic of China; 4College of Public Health, Medical and Veterinary Sciences, James Cook University, Townsville, QLD, AustraliaCorrespondence: Min Xu, Hospital Administration Department, The Second Affiliated Hospital of Shandong First Medical University, No. 366 Taishan Street, Taian, Shandong Province, 271000, People’s Republic of China, Tel +86-137-9112-0603, Email 13791120603@139.com Zhanming Liang, College of Public Health, Medical and Veterinary Sciences, James Cook University, JCU Townsville Campus, Douglas, Building 41, Room 217, Townsville, QLD, 4870, Australia, Tel +61-7-4781-5040, Email zhanming.liang@jcu.edu.auPurpose: Patient feedback plays a significant role in hospital service improvement. However, how to encourage patient feedback that can guide hospital service improvement is still being explored. By examining patient feedback data related to a tertiary hospital in China that was collected from the “ 12345” Government Service Convenience Hotline (GSCH), the paper discusses the learnings from GSCH in encouraging patient feedback and how quality improvement initiatives have effected the number and types of complaints made by patients and their families via GSCH.Methods: The study retrospectively collected and analyzed complaints on a Tertiary General University-affiliated hospital made via GSCH between 2016 and 2020. Patient care process-related complaints were coded using the health care complaint analysis tool (HCAT) and other complaint data were categorized based on the nature of the complaints. The autoregressive integrated moving average (ARIMA) models and mosaic plots were used to observe complaints trends and different complaint variables, respectively. The relationship between various quality improvement initiatives introduced since 2018 and patient complaints was also tested.Results: Close to 67% (n=2688) of calls made to the GSCH hotlines about the hospital were classified as a complaint including 60.6% vs 39.4% related to patient care process and nonpatient care process, respectively. For patient care process-related complaints, specifically against departments and personnel, 57.72% (n=961) were on clinical departments and 55.87% (n=471) were on doctors. Comparing the proportion of the complaint data in different categories in the two-year period of 2017– 2018 and 2019– 2020, an increase in management problems (47.73% vs 58.50%, P< 0.001) and decrease in relationship problems (33.65% vs 25.69%, P=0.002) were recorded.Conclusion: A unified, transparent, and impartial GSCH platform greatly encourages feedback from patients and families. Feedbacks provide evidence to guide health care organizations in improving the overall experience of patients and the quality of services that they provide.Keywords: patient feedback, medical service, hospital management, hotline, quality improvement, hospital services